Acoso escolar y su incidencia en el estado de ánimo de una adolescente de 15 años del Cantón Caluma - Cruz Santillan, Kelly Tatiana (2023)
In this present investigation of the case study, its objective is to know what the problem is, to obtain its respective psychotherapeutic treatment in addition to the anxious symptomatology and state of mind harming the 15-year-old adolescent. We also have the triangle of school bullying, that is to say, the observation of the profiles in which we find the aggressor, the victim and the spectators in the demonstration of this study, we came to know that the anxious levels of the victims are high, affecting the development of the affectivity in their activities, thus obtaining a low level of academic performance in addition to a depressed mood and feelings of guilt and emptiness, a series of tests were taken to detect the existing damage. I remember with the diagnostic criteria of the DSM5 generalized anxiety 300.02 F41.1. We see that the affectation of this pathology only harms the person as well as the social, academic, and family aspects involved, that is, with its symptoms such as nervousness, fatigue, chest pain, tachycardia, irritability, isolation, evasiveness, and lack of connection with the environment leads to a misunderstanding of the patient and her disorder.